Two new species of Baccharis subgen. Baccharis (Asteraceae, Astereae) with single-flowered female capitula from the Serra do Cipó, Minas Gerais, Brazil - Heiden, Gustavo; Pirani, José Rubens (Phytotaxa, 2014)
Two new species of Baccharis subgen. Baccharis endemic to the Serra do Cipó, south-eastern Brazil, are described and illustrated. Baccharis obdeltata is morphologically similar to the allopatric obdeltate-leaved B. truncata but is distinguished by its leaves with 3(–5)-dentate apex, fewer-flowered sessile capitula, the male capitula bearing 5–7 florets and the female capitula with solitary florets. Baccharis simplex resembles the sympatric B. concinna, from which can be differentiated by its oval to oblong leaves, with obtuse base and rounded to obtuse apex, and shorter female capitula, florets and cypselae. Illustrations, distribution map, habitat and conservation assessments are provided for the new species.